Food insecurity, coping strategies and glucose control in low-income patients with diabetes. Issue 6 (2nd September 2015) - Mayer, Victoria L; McDonough, Kevin; Seligman, Hilary; Mitra, Nandita; Long, Judith A
Abstract: Objective: To examine the relationship between food insecurity and coping strategies (actions taken to manage economic stress) hypothesized to worsen glucose control in patients with diabetes. Design: Using a cross-sectional telephone survey and clinical data, we compared food-insecure and food-secure individuals in their use of coping strategies. Using logistic regression models, we then examined the association between poor glucose control (glycated Hb, HbA1c≥8·0 %), food insecurity and coping strategies. Setting: An urban medical centre, between June and December 2013. Subjects: Four hundred and seven adults likely to be low income (receiving Medicaid or uninsured and/or residing in a zip code with >30 % of the population below the federal poverty level) with type 2 diabetes. Results: Of respondents, 40·5 % were food insecure. A significantly higher percentage of the food-insecure group reported use of most examined coping strategies, including foregone medical care, participation in the Supplemental Nutrition Assistance Program (SNAP)) and use of emergency food programmes. Food insecurity was associated with poor glucose control (OR=2·23; 95 % CI 1·22, 4·10); coping strategies that were more common among the food insecure were not associated with poor glucose control. Among the food insecure, receipt of SNAP was associated with lower risk of poor glucose control (OR=0·27; 95 % CI 0·09, 0·80). Conclusions: While food insecurity was associated with poor glucose control, most examined coping strategies did not explain this relationship. However, receipt of SNAP among food-insecure individuals was associated with better diabetes control, suggesting that such programmes may play a role in improving health.